PENGARUH PENGALAMAN PRAKTEK LAPANGAN KEPENDIDIKAN (PLK) TERHADAP KESIAPAN MENJADI GURU PADA MAHASISWA STKIP PESISIR SELATAN - Veni Veni; Sefrinal Sefrinal; Maijem Simponi (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
This study aims to determine the effect of the experience of the Educational Field Practice (PLK) on the readiness to become a teacher in the students of STKIP Pesisir Selatan.  This research is quantitative descriptive.  The population in this study was 31 students of STKIP Pesisir Selatan who had implemented PLK.  Data were collected through a questionnaire/questionnaire and analyzed using the Statistical Product and Service Solution (IBM SPSS Statistic 22) program.  The results showed that there was an influence between the experience of Educational Field Practice (PLK) on readiness to become a teacher, with a positive direction for students of STKIP Pesisir Selatan by 42.7%. The results of this study are expected to be used as reference material in improving the quality of education.